The influence of e-commerce as a marketing medium in increasing the income of MSMEs in Makassar city - Fitriany Fitriany (Institute of Computer Science (IOCS), 2023)
E-Commerce is an alternative in marketing that can improve income of MSMEs in the era of the Covid-19 pandemic. Where is the purpose of this research for determine the effect of e-commerce on MSME income. The research method uses multiple regression analysis method starting from the sampling technique using non probability sampling with the type of purposive sampling obtained as many as 180 samples of SMEs use e-commerce in their daily transactions. This research activity was carried out on 2022 with several stages of research starting from direct interviews with respondents study. The results of this study found that the effect of e-commerce is in this case Interface (interface), Navigation (Navigation), Content (Content) and Technical (Technical) positive and significantly to the increase in income of MSMEs in Makassar City while Reliability (Reliability) has a positive but not significant effect on increasing income at MSMEs in Makassar City.